Zur rüstungsökonomischen Bedeutung und groß raumwirtschaftlichen Motivation der Eingliederung der Sudetengebiete und Böhmen-Mährens in das Deutsche Reich [On the armament-economic significance and large-scale economic motivation of the integration of the Sudetenland and Bohemia-Moravia into the German Reich] - Volkmann, Hans-Erich (Studia Historiae Oeconomicae, 1979)
Hans-Erich Volkmann's article analyzes the economic and military-strategic motivations behind the incorporation of the Sudetenland and the regions of Bohemia and Moravia into the German Reich. Against the backdrop of growing economic pressure and the strategic goal of an autarkic war economy, Nazi leadership developed a clearly defined concept of a Großraumwirtschaft (greater economic space). This vision involved the systematic integration of resource- and labor-intensive territories in Central Europe as a prerequisite for the long-term success of German expansion and armaments policy. The aim of the study is to reconstruct the economic policy background and decision-making processes that led to the annexation, as well as to examine the specific armaments-related impacts of this territorial integration. The study draws on a wide array of contemporary sources, including files from the Reich Ministry of Economics, the Four-Year Plan, statistical data, and military planning documents. Key findings show that the Sudeten areas represented a valuable addition to the German economic sphere due to their industrial development, natural resources, and infrastructure. However, their immediate utility for the armaments sector was limited by structural shortcomings, a lack of existing military production facilities, and high investment requirements. In the long term, these regions were intended to serve as a bridgehead for economic expansion into Southeastern Europe. Volkmann concludes that economic motives – alongside ideological and power-political ones – played a central role in Nazi expansionism. The integration served both to secure strategic resources and to implement a hegemonic German-led economic order in Europe.